To Find or be Forgotten: Global Tensions on the Right to Erasure and Internet Governance. (1st January 2015) - Binoy Kampmark
Abstract : The decision of the Court of Justice of the European Union (CJEU) in Google Spain v AEPD and Mario Costeja González enshrined the "right to forget" in the jurisprudence of the European Union. The judgment caused concern to transparency and open information advocates in terms of pitting a right to forget against the general right of the public to know. This, as this paper will argue, is a false distinction. The Internet is, and has always been, a regulated space. Nor is the right to free expression, even in its American form, absolute. While there are genuine concerns about how the balance is struck, evolving practice is likely to identify what cases deserve deletion, to those that do not. The biggest challenge lies in how, and who, tests that balance as to what is removed from the search engines of the Internet. Finding material is important but forgetting may be just as vital to liberties as well.